THE GLOBAL STATUS OF ENGLISH LANGUAGE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
English has emerged as the predominant global language, serving as a primary medium in international communication, science, business, and education. This article examines the historical development of English’s global status, its dominance in scientific communication, and the implications for linguistic diversity and equity. It also explores initiatives aimed at promoting multilingualism in scholarly discourse.